Stakeholder Salience in Corporate Community Investment: Challenges to Community Participation in Developing Countries - Wood, Matthew (2014)
Corporate Community Investment (CCI) has become common practice for multinational companies operating in developing countries. It can serve not only to achieve a social license to operate from host communities, but also to further business interests through enhanced reputation, development of an employable local workforce, and avoidance of social unrest and conflict. This research looks at how members of a community impact upon the level of community participation in the arena of CCI. A case study of London Mining Company (LMC), an international iron ore extractor in Sierra Leone is used in order to explore how complex community structures determine which community stakeholders are engaged with, and the challenges that their salience creates in ensuring representative participation and effective dialogue between company and community.